THE VALUE OF LOCAL WISDOM IN THE CONTEXTUALIZATION OF BUDGETING IN ACEH - Suganda, Delfi; Murtazam, Teguh (Lambung Mangkurat Law Journal, 2019)
Aceh Province is a special area. Acts No. 11 of 2006 concerning the Government of Aceh provides freedom in terms of managing the government, especially regarding the implementation of Islamic law in Aceh. Islamic Shari’a is not only understood as a rule that regulates education, but also about regulation in government management in Aceh. One part of the government is about compiling regional spending in Aceh. This research is focused on budgeting which will be contextualized with Acehnese values, namely the local value of implementing Islamic law in Aceh. Priority indicators for a budget arrangement so that they fulfill the requirements as ideal budgets according to Islam (Islamic budget ideal). In terms of substance, this research is classified into qualitative research, which focuses on the depth and sharpness of the study. So if more quantitative research is on a broad, broad framework, the qualitative study is digging, swooping, and deep. Islamic budgeting is a value that in this context wants to be included in the budget in South Aceh. Based on the results of the study it was found that in terms of the determination of post-expenditure it is possible to include the values ​​of Islamic Shari’a. In this case the post expenditure is based on maqasid as-Syari’iyah. In terms of revenue, only zakat, shadaqah, and infaq are possible to be contextualized. As for ‘usyr, rikaz, etc., it is not possible because regional revenues from the fiscal side are regulated so rigid in state regulations